Development of Interactive Learning Media Using Animationand Educational Games of Solar System Materials Class VII - afaf 'Izzatunnafsi; Muhammad Luqman Hakim Abbas (JURNAL PEMBELAJARAN FISIKA, 2025)
Abstract: This research is motivated by the low learning outcomes of students on abstract Solar System materials and the limitations of conventional learning media based on the results of a needs analysis questionnaire, 77.8% of students experience difficulties in understanding Solar System materials, and 97.1% of students stated that they are more interested in learning using animation and games. This is an opportunity to present learning media that is interactive and fun. This research aims to (1) Develop PowerPoint-based interactive learning media using animation research and educational games on Solar System materials, (2) Determine the feasibility of the interactive learning media developed, (3) Determine the practicality of media in the learning process, and (4) Measure the effectiveness of media in improving student learning outcomes. Type and development (R&D) with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. The research was carried out at SMPN 1 Sumbergempol with 72 students in grades VII A and C. The results of the study showed that the media was successfully developed through the ADDIE stage, declared valid by material experts (85.83%) and quite valid by media experts (76.56%). The media was also practical (86.52%) and effective in improving learning outcomes, with the completeness of the experimental class being 80% compared to the control class of 54%, and statistical tests showed significant results (Asymp. Sig. 0.032; effect size 0.568). Keywords: Interactive Media; PowerPoint; Animation